Supramolecular photochemistry in beta-cyclodextrin hosts a TREPR, NMR, and CIDNP investigation - Krumkacheva, Olesya A (Langmuir : the ACS journal of surfaces and colloids, 2010)
A systematic investigation of the photochemistry and ensuing radical chemistry of three guest ketones encapsulated in randomly methylated beta-cyclodextrin (beta-CD) hosts is reported. Dibenzyl ketone (DBK), deoxybenzoin (DOB), and benzophenone (BP) triplet states are rapidly formed after photolysis at 308 nm. Time-resolved electron paramagnetic resonance (TREPR) spectroscopy, steady-state NMR spectroscopy, and time-resolved chemically induced nuclear polarization (TR-CIDNP) experiments were performed on the ketone/CD complexes and on the ketones in free solution for comparison. The major reactivity pathways available from these excited states are either Norrish I alpha-cleavage or H-atom abstraction from the interior of the CD capsule or the solvent. The DOB triplet state undergoes both reactions, whereas the DBK triplet shows exclusively alpha-cleavage and the BP triplet shows exclusively H-atom abstraction. Radical pairs are observed in beta-CDs by TREPR, consisting of either DOB or BP ketyl radicals with sugar radicals from the CD interior. The TREPR spectra acquired in CDs are substantially broadened due to strong spin exchange. The electron spin polarization mechanism is mostly due to S-T(0) radical pair mechanism (RPM) in solution but changes to S-T(-) RPM in the CDs due to the large exchange interaction. The TR-CIDNP results confirm the reactivity patterns of all three ketones, and DOB shows strong nuclear spin polarization from a novel rearrangement product resulting from the alpha-cleavage reaction